Scheduled maturation in low colorectal and coloanal anastomoses - Fernandes,Rubens Henrique Oleques (2016)
ABSTRACT Introduction: Anastomotic dehiscence is the main complication after low colorectal and coloanal anastomoses. The techniques commonly used are the double-stapling and hand-sewn anastomoses, both are made with immediate maturation. These techniques do not prevent pelvic sepsis in many patients and are not feasible in all cases. Objective: The study aim is to report the technical details and results with the use of scheduled maturation anastomosis in ten patients. Surgical technique: The scheduled maturation anastomosis is done in two steps. The first step is the closure of colonic stump in a way that keeps the mucosa layer in everted position. The second step is the union of the colon and rectum ends by transanal access. All the sutures are made with 2/0 polyglactin. A diverting stoma must be done in all cases. After 30 days, begins spontaneous opening of the anastomosis. Results: Ten patients underwent this technique. There were two cases of stenosis that were treated with digital dilatation in office. All patients had their diverting ostomy closed. Conclusion: The scheduled maturation anastomosis is feasible in difficult cases and may prevent pelvic sepsis in low colorectal and coloanal anastomoses.